Mediation of Marketing Capabilities in the Influence of Market Orientation, Entrepreneurial Marketing on the Marketing Performance of Small Businesses in Bogor City - Titiek Tjahja Andari; Ngadino Surip Diposumarto; Hari Muharam (Journal of World Science, 2025)
Small businesses play a vital role in Indonesia’s economic development, yet many still struggle to meet the dynamic demands of consumers. This study aims to examine the factors influencing the marketing performance of small businesses in Bogor City by applying both descriptive and verificative research methods. A survey was conducted on 350 respondents to explore the influence of market orientation, entrepreneurial marketing, and marketing capabilities on marketing performance, as well as the mediating role of marketing capabilities. Data was analyzed using Structural Equation Modeling (SEM) with LISREL 10.2 software. The findings indicate that market orientation and entrepreneurial marketing both significantly influence marketing capabilities. In turn, marketing capabilities, market orientation, and entrepreneurial marketing each have a significant direct impact on marketing performance. Furthermore, marketing capabilities mediate the relationship between market orientation and marketing performance and partially mediate the relationship between entrepreneurial marketing and marketing performance. The novelty of this research lies in the proposed mediation model, which links marketing capabilities as a critical pathway through which market orientation and entrepreneurial marketing affect marketing performance. The implications of these findings suggest that to enhance marketing performance, small business actors must prioritize strengthening their market orientation, particularly dimensions related to customer orientation. Measurement results show that customer orientation has the strongest correlation with market growth—specifically with increased sales and market share. Therefore, business owners’ commitment to understanding and responding to customer needs should be emphasized, as it directly supports the most significant performance outcomes in small business marketing.